"Soil Return" - Dias, Ana Margarida Rouxinol Sampaio (2021)
The circular economy is currently one of the European Union’s great strategic objectives, as it aims to achieve environmental, social and economic sustainability, without compromising the future of the European territory and the human communities that inhabit and interact with it. The consumption and subsequent production of domestic waste of families in industrialized countries has been gaining more prominence as one of the leading factors in modifiable pollution (UNEP 2010 – see Barbarrossa 2016). “Soil Return” is born as a solution to this issue. “Soil Return” is a user-oriented environmental technology project that consists of a small, easy-to-install and odorless container, which enables the rapid treatment of food residue produced in the preparation of home meals or in professional kitchens, through the compression and reduction of residue as well as the reuse of water in other applications. This project sets out to create a Business Plan based on the Business Model Canvas methodology proposed by Osterwalder and Pigneur (2011), which aims to evaluate the viability of the product, and a Business Management Plan conceived to allow a regular adaptation of the business model to the evolution of external circumstances, raising key questions and highlighting elements that could represent competitive advantages justified by Porter’s five forces.